A Poetics of Student Writing - Dennis Young (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Focusing on student reflective essays about learning writing, I rely on depth psychology and hermeneutics to illustrate the image-making, poetic dimension of student work.